2007
DOI: 10.1021/es062113+
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Metals on the Sorption of Hydrophobic Organic Compounds to Wood Charcoal

Abstract: Black carbon (BC) is believed to be an important adsorbent of organic pollutants. A complex suite of heavy metals and organic pollutants is commonly present in many situations. An issue that has received little direct attention is the effect of heavy metals on sorption of organic compounds to BC. We found that coadsorption of Cu2+ at an environmentally relevant, comparable concentration (50 mg L-1) decreases sorption of both the polar compound, 2,4-dichlorophenol (DCP), and nonpolar compounds, 1,2-dichlorobenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(112 citation statements)
references
References 30 publications
7
105
0
Order By: Relevance
“…It is generally recognized that hydration reactions become more important if hydrated metals and adsorbent micropores have comparable sizes (12). As an example, the micropore and mesopore data for ash (SI Figure S7) indicated that micropores of 2.5-15 Å account for 65.6% of cumulative micropore and mesopore volumes.…”
Section: Nmr Spectra and Elementalmentioning
confidence: 99%
“…It is generally recognized that hydration reactions become more important if hydrated metals and adsorbent micropores have comparable sizes (12). As an example, the micropore and mesopore data for ash (SI Figure S7) indicated that micropores of 2.5-15 Å account for 65.6% of cumulative micropore and mesopore volumes.…”
Section: Nmr Spectra and Elementalmentioning
confidence: 99%
“…For example, several workers have suggested that heavy metals can enhance or inhibit the sorption of HOCs to carbonaceous materials depending on the composition and structure of the sorbents (7,8). Combined contamination by heavy metals and organic contaminants often occurs in the soil environment (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Ag + is highly polarizable and can bind with aromatic organic compounds containing π-electrons (Chen et al 2007), resulting in further elevated TCP adsorption by ash. In addition, Ag + has one positive charge and a larger ionic radius than Zn 2+ and Al 3+ ; hence, it is relatively easier for Ag + to replace the metal ions (mainly solonetz metal ions such as Na + and Ca 2+ ) originally on ash through outer layer complexation reactions (Chen et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Ag + is highly polarizable and can bind with aromatic organic compounds containing π-electrons (Chen et al 2007), resulting in further elevated TCP adsorption by ash. In addition, Ag + has one positive charge and a larger ionic radius than Zn 2+ and Al 3+ ; hence, it is relatively easier for Ag + to replace the metal ions (mainly solonetz metal ions such as Na + and Ca 2+ ) originally on ash through outer layer complexation reactions (Chen et al 2007). This will lead to further reduction in the solubility of functional groups on the ash surface and also compress the hydrated ionic radius of these metal ions, thereby reducing the competitive adsorption of water molecules on the ash surface and increasing the adsorption of TCP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation